Overlap syndromes: the International Autoimmune Hepatitis Group (IAIHG) position statement on a controversial issue. - Boberg, K; Chapman, R; Hirschfield, G; Lohse, A; Manns, M; Schrumpf, E (2011)
Some patients present with overlapping features between disorders within the spectrum of autoimmune liver diseases (i.e. autoimmune hepatitis (AIH), primary biliary cirrhosis (PBC), and primary sclerosing cholangitis (PSC)) and are commonly classified as having an "overlap syndrome". Standardized definitions of "overlap syndromes" are lacking. The aim of this report by the International Autoimmune Hepatitis Group (IAIHG) is to evaluate if there are important reasons to classify conditions with overlapping features between autoimmune liver diseases as separate diagnostic entities. Definition of diagnostic criteria for overlap conditions can only be arbitrary. The IAIHG scoring system for diagnosis of AIH has been widely used to diagnose "overlap syndromes", but was not intended for such use and has not proven to be an efficient tool for this purpose. Some patients with overlapping features between a cholestatic and hepatitic disorder appear to benefit from treatment with a combination of ursodeoxycholic acid and immunosuppressants, but this strategy is not evidence-based, and it seems unjustified to define new diagnostic groups in this regard. The IAIHG suggests that patients with autoimmune liver disease should be categorized according to the predominating feature(s) as AIH, PBC, and PSC/small duct PSC, respectively, and that those with overlapping features are not considered as being distinct diagnostic entities. The IAIHG scoring system should not be used to establish subgroups of patients. Patients with PBC and PSC with features of AIH should be considered for immunosuppressive treatment. Due to the low prevalence of such "overlap syndromes", prospective interventional therapeutic trials cannot be expected in the foreseeable future.